Pengembangan Inovasi Kemasan Dan Pembukuan Sederhana Dengan Sistem Digitalisasi Pada Pelaku UMKM Ery Noer Craft Di Kelurahan Prapatan - Dewi Sartika; Fitri Adijaya; Andi Nurfita; Niken Cahya Ningtyas; Vermaysuri Cahya Ningrum (STIKes Ibnu Sina Ajibarang, 2023)
Field Work Practice (PKL) or also known as Innovation Development (PI) is a service activity of STIE Madani Balikpapan students to the community, especially to Micro, Small and Medium Enterprises (MSMEs). The MSME target for the Innovation Development Program (PI) in this group is Ery Noer Craft which is located in RT 27 Prapatan Village, Balikpapan City District. The aim of this PI activity is to assist in the creation of product packaging innovations that are more attractive and safe. Apart from that, it also helps in assisting in recording simple financial reports through a digitalization system.